Coordination Models and Languages 17th IFIP WG 6.1 International Conference, COORDINATION 2015, Held as Part of the 10th International Federated Conference on Distributed Computing Techniques, DisCoTec 2015, Grenoble, France, June 2-4, 2015, Proceedings - Holvoet, Tom; Viroli, Mirko (Programming and Software Engineering, 2015)
This book constitutes the refereed proceedings of the 17th International Conference on Coordination Models and Languages, COORDINATION 2015, held as part of the 10th International Federated Conference on Distributed Computing Techniques, DisCoTec 2015, in Grenoble, France, in June 2015. The 14 full papers and one short paper presented were carefully reviewed and selected from 36 submissions. They are organized in topical sections on tuple-based coordination, coordinating ensembles, constraints, agent-oriented techniques and shared spaces.